อิทธิพลของลักษณะชุมชนต่อโมเดลการส่งเสริมการออม ของผู้สูงอายุในจังหวัดนนทบุรีตามหลักปรัชญาเศรษฐกิจพอเพียง: โมเดลสมการโครงสร้างกลุ่มพหุ - อังศุโชติ, สุภมาส (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2016)
การวิจัยนี้มีวัตถุประสงค์เพื่อพัฒนาและตรวจสอบความตรงของโมเดลการส่งเสริมการออมของผู้สูงอายุในชุมชนเมืองและชุมชนชนบทของจังหวัดนนทบุรีตามหลักปรัชญาเศรษฐกิจพอเพียง และศึกษาอิทธิพลของลักษณะชุมชนต่อโมเดลการส่งเสริมการออมของผู้สูงอายุในจังหวัดนนทบุรีตามหลักปรัชญาเศรษฐกิจพอเพียง กลุ่มตัวอย่างประกอบด้วย ผู้สูงอายุจำ 690 คน ที่สุ่มแบบหลายขั้นตอนจากผู้สูงอายุใน 48 ตำบล 5 อำเภอของจังหวัดนนทบุรี โดยแยกเป็นผู้สูงอายุในชุมชนเมือง 312 คน และผู้สูงอายุในชุมชนชนบท 378 คน เครื่องมือที่ใช้ในเก็บรวบรวมข้อมูลคือแบบสอบถาม การวิเคราะห์ข้อมูลใช้การวิเคราะห์โมเดลสมการโครงสร้าง และโมเดลสมการโครงสร้างกลุ่มพหุผลการวิจัยพบว่า (1) โมเดลการส่งเสริมการออมของผู้สูงอายุในชุมชนเมืองและชุมชนชนบทของจังหวัดนนทบุรีตามหลักปรัชญาเศรษฐกิจพอเพียงสอดคล้องกลมกลืนกับข้อมูลเชิงประจักษ์ในเกณฑ์ดี โดยมีค่า χ2=155.64, df=79, p-value=0.000, χ2/df = 1.97, GFI=0.97, AGFI=0.95, CFI=0.99, RMSEA=0.038, SRMR=0.035 ปัจจัยเชิงสาเหตุที่ผู้วิจัยคัดสรรมาอธิบายความแปรปรวนของการออมของผู้สูงอายุในชุมชนเมืองและชุมชนชนบทของจังหวัดนนทบุรีได้ร้อยละ 55 ปัจจัยที่มีอิทธิพลทางบวกต่อการออมของผู้สูงอายุในจังหวัดนนทบุรีอย่างมีนัยสำคัญทางสถิติที่ระดับ .01 เรียงลำดับจากมากไปหาน้อย ได้แก่ สถานภาพทางการเงิน (β=0.93) และลักษณะส่วนบุคคล (β=0.31) ส่วนปัจจัยที่มีอิทธิพลทางบวกต่อการออมของผู้สูงอายุในจังหวัดนนทบุรีอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 ได้แก่ การปฏิบัติตนตามหลักปรัชญาเศรษฐกิจพอเพียง (β=0.10) ส่วนการเป็นสมาชิกกลุ่มการออมในชุมชนไม่มีอิทธิพลต่อการออมของผู้สูงอายุในชุมชนเมืองและชุมชนชนบทของจังหวัดนนทบุรี (β=0.04) (2) โมเดลการส่งเสริมการออมของผู้สูงอายุในชุมชนเมืองและชุมชนชนบทของจังหวัดนนทบุรีตามหลักปรัชญาเศรษฐกิจพอเพียงมีความสอดคล้องกันในด้านรูปแบบโมเดล โดยมีค่า χ2=498.017, df=183, p-value=0.000, χ2/df = 2.72, CFI = 0.93, NNFI = 0.91, RMSEA = 0.071 This research aimed to develop and examine the accuracy of saving encouragement model of elders in city and rural area in Nonthaburi province based on sufficiency economy theory, and to study the infl uences of community type on saving encouragement model of elders in Nonthaburi province based on the sufficiency economy theory. Samples were 690 elders which selected randomly by multistage random sampling from 48 sub-districts of 5 districts in Nonthaburi province. They can be divided into two groups, i.e. 312 from the city and 378 from rural area. Data was collected by questionnaire and analyzed by multi-group structural equation modeling. The results of the research found that (1) saving encouragement model of elders in city and rural area in Nonthaburi province bases on sufficiency economy theory related well to empirical data, which was confirmed by χ2 =155.64, df=79, p-value=0.000, χ2/df = 1.97, GFI=0.97, AGFI=0.95, CFI= 0.99, RMSEA=0.038, SRMR=0.035. 55 percent of saving variances of elder in city and rural area in Nonthaburi province were from Causal factors. The positive factors had statistical significance at .01 were fi nancial status (β=0.93) and personal character (β=0.31). Moreover, the positive factor had statistical significance at .05 was behaving base on the sufficiency economy theory. (β=0.10) On the contrary, becoming a member of saving group did not influence on saving of elders in city and rural area in Nonthaburi province (β=0.04). (2) Saving encouragement model of elders in city and rural area in Nonthaburi province based on sufficiency economy theory was identical with the model, which was comfirmed by χ2=498.017, df=183, p-value=0.000, χ2/df = 2.72, CFI = 0.93, NNFI = 0.91, RMSEA = 0.071. it can be said that the positive factor of elders in the city that had statistical significance at .01 was financial status (β=0.98).